2016
DOI: 10.1017/s0016756816000261
|View full text |Cite
|
Sign up to set email alerts
|

Insights into a million-year-scale Rhenohercynian carbonate platform evolution through a multi-disciplinary approach: example of a Givetian carbonate record from Belgium

Abstract: Background: In this research we formulate answers to three important questions related to Givetian carbonate records and their use for reconstructing million-year-scale past palaeoenvironmental changes. First, we provide detailed illustrations of the fascinating diversity that shaped a significant shallow reefal platform during early to late Givetian time in the Rhenohercynian Ocean; secondly we improve the sedimentological model of the extensive Givetian carbonate platform in the Dinant Basin; and thirdly we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 61 publications
(107 reference statements)
1
27
0
Order By: Relevance
“…In this study, a more likely explanation for the P16 antiphase relation in Mg, Sr and Ba is the incongruent dissolution of dolomite (CaMg(CO3)2; IDD), taking place during annual periods that are characterized by enhanced water-rock interaction. The presence of dolomite within lateral-equivalent Givetian limestone deposits in Belgium has been recognised by Pas et al (2016). Dolomitized parts of the limestone host-rock were observed within the nearby Père-Noël Cave (Fairchild et al, 2001).…”
Section: Magnesium Strontium and Barium Proxiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, a more likely explanation for the P16 antiphase relation in Mg, Sr and Ba is the incongruent dissolution of dolomite (CaMg(CO3)2; IDD), taking place during annual periods that are characterized by enhanced water-rock interaction. The presence of dolomite within lateral-equivalent Givetian limestone deposits in Belgium has been recognised by Pas et al (2016). Dolomitized parts of the limestone host-rock were observed within the nearby Père-Noël Cave (Fairchild et al, 2001).…”
Section: Magnesium Strontium and Barium Proxiesmentioning
confidence: 98%
“…Within the Mont-d'Haurs Fm., the biostromal limestones are alternated with fine-grained micritic limestones and dolomitic shales (Preat and Bultynck, 2006). Additionally, a recent study by Pas et al (2016) on Middle Devonian outcrops has shown that dolomitized beds also occur within the limestones of the Fromelennes Fm.…”
Section: Han-sur-lesse Cavementioning
confidence: 99%
“…The second case study consists of the 184 m thick continuous early Givetian to early Frasnian sequence of the La Thure section (∼ 383-380 Ma, Middle-Late Devonian; De Vleeschouwer and Parnell, 2014;De Vleeschouwer et al, 2015;Pas et al, 2016). The Givetian sequence is composed of bedded limestone, mainly deposited in a shallow-water rimmed shelf characterised by a large set of internal and external rimmed-shelf environments (Pas et al, 2016).…”
Section: The Geological Datasetsmentioning
confidence: 99%
“…The Givetian sequence is composed of bedded limestone, mainly deposited in a shallow-water rimmed shelf characterised by a large set of internal and external rimmed-shelf environments (Pas et al, 2016). The overlying early Frasnian sequence is dominated by shale deposited in a siliciclastic drowned platform .…”
Section: The Geological Datasetsmentioning
confidence: 99%
“…In this study, multiple proxies, such as sedimentology, geochemistry and hysteresis magnetic measurements are generated from the million year Fromelennes-Flohimont section in France (southern margin of the Ardennes platform). These data are then integrated with previously published data from the northern margin of the Ardennes platform [La Thure (LT) section] which include facies, geochemistry (Pas et al, 2017) and magnetic susceptibility analyses (De Vleeschouwer et al, 2015). This synthesis sheds new light on the depositional environments, their variations across the platform and the main sea-level fluctuations from the earliest to the latest Givetian time.…”
Section: Introductionmentioning
confidence: 99%